An Examination of South African Corporate Law Through the Lens of Ubuntu - Siphethile Phiri (Obiter, 2024)
This article submits that ubuntu is indubitably a constitutional value that informs the constitutional epoch. Constitutional supremacy means that all values and principles of the Constitution must be observed to avoid invalidation. In light of this constitutional obligation, this article intends to examine the inclusion of ubuntu as a constitutional principle in South African corporate law. To achieve this objective, the article employs doctrinal legal research methodology, also known as black-letter law, which encompasses extensive scrutiny of relevant legal literature. This research methodology is selected owing to its ability to address the question of what the law is in a particular case. The article intends to determine the position of ubuntu as a constitutional principle in the context of South African corporate law. The conclusion reached is that South African corporate law contains significant traces of the ontological elements of ubuntu. This is reinforced by a clear correlation between the values of ubuntu and corporate law principles. Simply put, several South African corporate-law concepts appear to be founded on the influence of ubuntu – for instance, the exception to the cornerstone principle of juristic personality. The lifting of the corporate veil aims to avoid unconscionable abuse of the corporate structure, which is in line with the ubuntu principles, which operate against any form of unconscionable abuse, as defined in common law. Nonetheless, since there is still no express inclusion of ubuntu in the Constitution or corporate statutes, the conclusions reached in this article are based on its implied application.